A comparative study on the performance of partially premixed combustion (PPC), reactivity-controlled compression ignition (RCCI), and RCCI with reverse reactivity stratification (R-RCCI) fueled with gasoline and polyoxymethylene dimethyl ethers (PODEn). (15th August 2021) - Duan, Huiquan; Jia, Ming; Li, Yaopeng; Wang, Tianyou
Highlights: The potential of R-RCCI was demonstrated by comparing with PPC and RCCI. R-RCCI has the highest ITE compared with PPC and RCCI. R-RCCI has very low soot emissions at both low and medium loads. The reasons for the great advantages of R-RCCI were explained in detail. Abstract: To solve the challenges of the high heat release rate of partially premixed combustion (PPC) and low combustion efficiency of reactivity-controlled compression ignition (RCCI), RCCI with reverse reactivity stratification (R-RCCI) fueled with gasoline and polyoxymethylene dimethyl ethers (PODEn ) was investigated at low and medium loads in a light-duty compression-ignition engine in this study. The results indicated that R-RCCI has moderate combustion rate and combustion efficiency between PPC and RCCI. At both low and medium loads, R-RCCI has the highest indicated thermal efficiency (ITE) due to its relatively lower heat transfer losses compared with PPC. Moreover, the nitrogen oxides (NOx ) and soot emissions of R-RCCI are significantly lower than that of PPC. Although RCCI has the lowest heat transfer losses, its considerably low combustion rate leads to substantial exhaust losses and thereby yields a low ITE. Compared with RCCI, R-RCCI has a better balance between the degree of premixed combustion and combustion temperature, which is crucial for soot oxidation, so it has very low soot emissions at both low and medium loads.